Exercise for dementia and Mild Cognitive Impairment: methodological considerations - Juan Tortosa-Martínez; Nuria Caus; Celeste Martínez-Canales; Miguel García-Jaén (Asociación Española de Ciencias del Deporte, 2018)
The exponential worldwide increase in the number of older adults is causing a parallel rise in the number of cases of neurodegenerative diseases, such as mild cognitive impairment (MCI) and dementia. Exercise is a promising strategy for improving physical and cognitive function in healthy older adults, reducing the risk of developing MCI and dementia, and improving physical and cognitive function as well as decreasing neuropsychiatric symptoms in people with MCI and dementia. However, there are still some inconsistencies in the literature, especially in regards to the cognitive benefits, and there are currently no guidelines for prescribing exercise for older adults with cognitive impairment. In this article, a narrative review on the benefits of exercise for people with MCI and dementia was conducted, establishing some preliminary guidelines for prescribing exercise efficiently and safely in this population.